OPTIMASI KELAJUAN PEMANASAN PADA EKSTRAKSI SILIKON DIOKSIDA (SiO2 ) DARI SEKAM PADI - , Masrur (Jurnal Biofisika, 2013)
According to Central Agency Statistics Indonesia,  production rice in 2012 will reach 69.05 million ton. Seeing this, it would appear the main agricultural waste generated from  rice,  the  rice  husk.  Rice  husk  ash  has  the  potential  to  produce  silica. Incineration process of rice husk was performed in a furna ce at temperature of 400oC for  2  hours  and  950oC  for  1  hour,  with  the  increase  rate  0.5oC/minute  and 1.5oC/minute.  The  incineration  yield  then  washed  with  Chloride  acid  3%  (12  mL Chloride  acid  3%  for  1  gram  of  rice  husk  ash)  and  heated  using  hotplate  and magnetic stirrer, with a speed of 240 rpm for 2 hours at 200oC. Furthermore sample washed repeatedly using hot distilled water until free acid using litmus papers, then reheated  in  a  furnace  to  produce  silica.  EDX  results  for  silicon  dioxide  of  about 99.15% (for increase rate 0.5 oC/minute) and 78.96% (for increase rate 1.5oC/minute). Characterization  of  the  silica  using  FTIR  spectroscopy  revealed  the  existence  of functional group (siloxane). Peaks of FT-IR spectrum showed specific peaks related to the present of SiO2 at the wave number range of 1.110 cm-1 to 467 cm-1